1998
DOI: 10.1016/s1074-7613(00)80538-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interaction of CD1b with Lipoglycan Antigens

Abstract: The ability of human CD1b molecules to present nonpeptide antigens is suggested by the T cell recognition of microbial lipids and lipoglycans in the presence of CD1b-expressing antigen-presenting cells. We demonstrate the high-affinity interaction of CD1b molecules with the acyl side chains of known T cell antigens, lipoarabinomannan, phosphatidylinositol mannoside, and glucose monomycolate. Furthermore, CD1b-antigen binding was optimal at acidic pH, consistent with the known requirement for endosomal acidific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
134
0
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 37 publications
14
134
0
2
Order By: Relevance
“…Similar to processing/presentation of MHC class II-restricted protein Ags, chloroquine inhibits CD1b-mediated T cell stimulation (5,28,29). Moreover, the CD1b molecule accommodates its ligands more efficiently when loading is performed at low pH, which probably facilitates widening of the groove (30). It can also be speculated that glycolipids are processed by host cell-derived lysosomal enzymes, which have lower pH optima.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to processing/presentation of MHC class II-restricted protein Ags, chloroquine inhibits CD1b-mediated T cell stimulation (5,28,29). Moreover, the CD1b molecule accommodates its ligands more efficiently when loading is performed at low pH, which probably facilitates widening of the groove (30). It can also be speculated that glycolipids are processed by host cell-derived lysosomal enzymes, which have lower pH optima.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the structurally different parietal and cellular ManLAM PI anchors differentially stimulate interleukin-8 and tumour necrosis factor-α secretion from human dendritic cells [11]. Moreover it is likely that PI anchor plays a crucial role in ManLAM presentation to αβT cells by CD1 molecules [41]. CD1 glycoproteins are characterized by a hydrophobic groove which corresponds to the antigen-binding site [20].…”
Section: Discussionmentioning
confidence: 87%
“…CD1 glycoproteins are characterized by a hydrophobic groove which corresponds to the antigen-binding site [20]. It is quite clear that ManLAM binding to CD1 occurs through the hydrophobic interactions between ManLAM fatty acids and non-polar amino acids of the CD1 groove [41]. So, subtle differences in the PI anchor concerning the degree of acylation (from 1 to 4 fatty acids), the acylation site (glycerol, Manp, myo-inositol) and the nature of the fatty acids [palmitic, tuberculostearic, stearic, 12-O-(methoxypropanoyl)-12-hydroxystearic acids], probably discriminate ManLAM CD1 binding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, both CD1b and MHC class II molecules may load Ags in the same types of late endosomal compartments (13). Late endosomes are thought to possess a milieu amenable to the loading of CD1b with Ags, given their acidic pH and the presence of CD1b-binding Ags (11,13,14,30). Significantly, only a minority of GPI-anchored molecules, which lack a cytoplasmic tyrosine-based targeting motif, transit into this late endosomal compartment that is thought to be essential for CD1b Ag loading.…”
Section: Discussionmentioning
confidence: 99%